Analysis of financial performance measurement of indonesia airport companies case studies of pt angkasa pura i and pt angkasa pura ii in the period of 2011-2017 - Ibnu Sina, Andy; M. Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2019)
Abstract. In 2014, Indonesia government started focus on tourism sector by targeting to 20 million foreign tourists and 275 million domestic tourists in 2019. The target expected in 2019, the tourism sector could contribute 15% of total GDP. In order to the target could be achieved, Indonesia government is conducting accelerate of airport infrastructure development. The government targeted the construction of 14 new airports throughout Indonesia and part of target has been completed in 2017. PT Angkasa Pura I and PT Angkasa Pura II are as state-owned enterprises (SOE) that managing the airport in Indonesia must be able to support the government’s policy. The government’s focus on the tourism sector and infrastructure is an opportunity for companies to improve their company performance by looking at their financial performance. The government’s focus has been running for almost four years, how the financial health of the two SOEs is by measuring eight financial ratios based on the Ministry of SOE Decree No. Kep-100/MBU/2002 concerning health assessment of SOE. The eight financial ratios are Return on Equity, Return on Investment, Cash Ratio, Current Ratio, Collection Period, Inventory Turnover, Total Assets Turnover, and Total Equity to Total Assets. There are three levels on health assessment namely healthy (AAA,AA,A), less healthy (BBB,BB,B), and not healthy (CCC,CC,C). The results of the assessment of the eight ratios from 2011-2017 can be concluded that the financial health of PT Angkasa Pura I is in the healthy category and tend to be increased (from BBB to A). While the financial health of PT Angkasa Pura II is in a healthy category but tend to be decreased (from AA to A). For the last seven years, financial performance of PT Angkasa Pura I was better than PT Angkasa Pura II because of an increase in the category of financial health. Keyword: Financial Performance, Financial Ratio, Financial Health, State-Owned Enterprises, Airport.